Dampak Penggunaan Gadget Terhadap Psikologi Anak Balita di Desa Laut Dendang - Sihombing, Sulaiman (Institut Agama Islam Negeri Padangsidimpuan, 2024)
The aim of this research is to determine the impact of using gadgets on children under five in Laut Dendang Village. This research uses a descriptive qualitative approach. The data sources in this research are primary data and secondary data. The results of this study show that the impact of using gadgets on the psychology of children under five in Laut Dendang Village is not good or has a greater negative impact because it can make children addicted to gadgets and have uncontrolled emotions or tantrums in children. During the toddler years, children must focus on exploring their surroundings because this will have an impact on their thinking power in the future.